Environmental factors influencing eastern North Pacific gray whale calf production 1994–2016. Issue 2 (30th October 2020) - Perryman, Wayne L.; Joyce, Trevor; Weller, David W.; Durban, John W.
Abstract: This paper describes the relationship between eastern North Pacific gray whale calf production and environmental conditions in the Pacific Arctic where they feed. The results show how interannual variation in sea ice cover in the Bering and Chukchi Seas along with broader indices of North Pacific climate, such as Pacific Decadal Oscillation (PDO) and North Pacific Index (NPI), are linked to variation in gray whale reproductive output. Estimates of gray whale calf production were derived from 23 consecutive years (1994–2016) of shore‐based visual surveys conducted off California during the northward migration. PDO and NPI in combination with ice cover in the Bering and Chukchi Seas during the early phase of gestation appear to be important in explaining the observed variability in calf production. Of the 2, 285 time series linear models evaluated, the model of best‐fit included PDO(July), Ice(June), NPI(February), and explained 60% of the observed variability in calf production. After elimination of two data outliers in calf production estimates (2013 and 2014) a model including Ice(May), PDO(May), and NPI(July) explained 90% of the variability. We conclude that access to prey early in the gestation period is critical to reproductive success in this population and may be important for other capital breeding mammals.